Phytochemistry of compounds isolated from the leaf-surface extract of Psiadia punctulata (DC.) Vatke growing in Saudi Arabia. (November 2018) - Dal Piaz, Fabrizio; Bader, Ammar; Malafronte, Nicola; D'Ambola, Massimiliano; Petrone, Anna Maria; Porta, Amalia; Ben Hadda, Taibi; De Tommasi, Nunziatina; Bisio, Angela; Severino, Lorella
Abstract: The surface extract of an accession of Psiadia punctulata (DC.) Vatke (Asteraceae) growing in Saudi Arabia was investigated for its phytochemical composition. A bio-guided investigation of the extract led to the isolation of thirteen ent -kaurane and trachylobane diterpenes and seventeen compounds previously described, including nine flavonoids and eight diterpenes. Three flavonoids and one ent -kaurane diterpene showed antimicrobial activity with MIC100 values ranging from 25 to 150 μg/ml. The extract showed antibacterial activity against Staphylococcus aureus (MIC100 = 180 μg/ml) and antifungal activity against Candida albicans (MIC0 = 130 μg/ml). The isolated 3′, 4′, 5, 7-tetramethoxyflavone, at a concentration of 40 μg/ml, displayed the ability to reduce biofilm formation of S. aureus and C. albicans by 50% and 90% respectively. Graphical abstract: Highlights: The surface extract of Psiadia punctulata from Saudi Arabia was investigated. Thirteen previously undescribed ent -kaurane and trachylobane diterpenes were isolated. Nine known flavonoids and eight known diterpenes were also isolated. The antimicrobial activity of the extracts, fractions and isolates was evaluated.